Polifenoli v različnih vrstah macesna (Larix spp.) - Zule, Janja (Zbornik gozdarstva in lesarstva, 2008)
Various types of polyphenolic compounds, such as lignans, oligolignans and flavonoids, which occur in different tissues of wood from the larch (Larix) genus, are presented in the article. Their biosynthesis, chemical structure and properties, including a distinctive antioxidative potential, are described. The methods of quantitative isolation from wood as well as their chemical characterization by means of sophisticated chromatographic analytical techniques are presented. It has been experimentally established that the highest concentrations of lignans and flavonoids are present in knots, branches and bark of trees. The most important flavonoid in larch tissues is taksifolin, while the predominating lignans in knots are secoisolariciresinol and less abundant lariciresinol and cycloisolariciresinol. The presence of polyphenols is crucial for wood durability, as these compounds represent efficient chemical protection of wood against biological decay. Due to high concentrations of bioactive lignans in knots of conifers, the latter represent a suitable source for technological production of valuable substances.
Keywords: antioksidanti; antioxidant; flavonoidi; Larix spp.; lignani; macesen; polifenoli